2011
DOI: 10.1093/infdis/jir352
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of SerpinB1 in Regulating Inflammatory Responses in Pulmonary Influenza Infection

Abstract: Because viral clearance was unimpaired, the study highlights the critical role of serpinB1 in mitigating inflammation and restricting pro-inflammatory cytokine production in influenza infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…[12][13][14]49 In this context, we have previously shown that serpinB1 contributes to prevent increased mortality and morbidity associated with production of inflammatory cytokines upon infection with Pseudomonas aeruginosa and influenza A virus. 20,50 In this study, we demonstrate that serpinB1 inhibition of the primary granule protease CG in PMNs is essential for PMN survival and this ultimately regulates PMN numbers in vivo. Our findings also extend the roles of CG from antimicrobial and immunoregulatory functions to a novel role in inducing cell death.…”
Section: Discussionmentioning
confidence: 65%
“…[12][13][14]49 In this context, we have previously shown that serpinB1 contributes to prevent increased mortality and morbidity associated with production of inflammatory cytokines upon infection with Pseudomonas aeruginosa and influenza A virus. 20,50 In this study, we demonstrate that serpinB1 inhibition of the primary granule protease CG in PMNs is essential for PMN survival and this ultimately regulates PMN numbers in vivo. Our findings also extend the roles of CG from antimicrobial and immunoregulatory functions to a novel role in inducing cell death.…”
Section: Discussionmentioning
confidence: 65%
“…These results indicated that SERPINB1 promoted STAT3/HO-1 activation to confer its pulmonary protective effects in ALI was through ERK1/2. number than that of wild-type mice, which associated with elevated cytokines and chemokines concentrations in the lung 34 . Results from our current study provided additional evidences that SERPINB1 conferred pulmonary protection not only through its anti-inflammatory effects but also from its antioxidant property.…”
mentioning
confidence: 90%
“…Neutrophils are protected by serpinB1 from a cellintrinsic death pathway mediated by CG, which induces neutrophil death both upstream and independently of caspases (2,4). In highly acute neutrophil inflammation caused by bacterial and viral infections, we showed that reduced neutrophil survival led to an overwhelming inflammation, increased tissue injury, and, ultimately, increased mortality in serpinB1a KO mice (5,20). In the emphysema model, neutrophil recruitment is considerably lower than in infectious settings, and the rapid demise of neutrophils may ultimately be less damaging, and thus, not associated with increased lung damage in KO mice after cigarette smoke exposure.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, rats or serpinB1a-deficient mice treated with recombinant SERPINB1 showed increased Pseudomonas clearance and reduced associated inflammation (5,55). In addition, serpinB1a-deficient mice showed increased lung injury, morbidity, and mortality following influenza A virus infection (20). These findings demonstrate that SERPINB1 is a critical regulator of neutrophil proteases during lung infection.…”
mentioning
confidence: 77%